2017
DOI: 10.1002/epi4.12089
|View full text |Cite
|
Sign up to set email alerts
|

Young people with epilepsy have an increased risk of eating disorder and poor quality diet

Abstract: SummaryObjectiveTo investigate whether adolescents with epilepsy are at increased risk of having self‐reported eating disorder symptoms and poor quality diet compared to young people from the general population.MethodsWe used data from the Health Profile for Children and Youth in Akershus Study, a cross‐sectional population‐based study based on a voluntary self‐reported questionnaire. There were 19,995 participants (response rate 85%) aged 13–19 years; 247 (1.2%) reported a lifetime diagnosis of epilepsy. Odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Indeed, a study in Australian general population revealed that the prevalence of anorexia nervosa and bulimia nervosa was less than 1% whereas those of binge eating disorder and subthreshold binge eating disorder were 5.6-6.9% [33]. Another two studies using self-report nondiagnostic questionnaires also illustrated that around 5% of PWE had eating disorder symptoms [11,34]. Since the M.I.N.I was designed to detect merely anorexia nervosa and bulimia nervosa, but not other eating disorders, these evidence could imply that the former two disorders are much less common in PWE than binge eating disorder as well as subthreshold eating disorder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a study in Australian general population revealed that the prevalence of anorexia nervosa and bulimia nervosa was less than 1% whereas those of binge eating disorder and subthreshold binge eating disorder were 5.6-6.9% [33]. Another two studies using self-report nondiagnostic questionnaires also illustrated that around 5% of PWE had eating disorder symptoms [11,34]. Since the M.I.N.I was designed to detect merely anorexia nervosa and bulimia nervosa, but not other eating disorders, these evidence could imply that the former two disorders are much less common in PWE than binge eating disorder as well as subthreshold eating disorder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a questionnaire for 19,995 participants, including 247 with epilepsy, showed that adolescents with epilepsy had a higher risk of FEDs, unhealthy eating, and less satisfaction with their appearance. Male adolescents with epilepsy had a higher risk of dieting (OR 3.1) and less satisfaction with their appearance (OR 0.4), while females with epilepsy had an increased risk of unhealthy eating [ 55 ]. The influence of antiepileptic therapy on the risk of developing symptoms of altered feeding could be due to both metabolic and psychotropic effects [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esto concuerda con estudios como los de Kolstad et al, quien encontró que los pacientes pediátricos con epilepsia tienen mayor riesgo de trastornos alimenticios y consumo de dietas de baja calidad. 15 En cuanto a los factores de riesgo para epilepsia, es conocido que los países de la región tienen mayor frecuencia de infecciones, lesiones perinatales y el manejo no adecuado de las crisis epilépticas en la infancia. 16 Estos datos concuerdan con los hallazgos de nuestro estudio, 22.4% (75) de los pacientes tenía antecedente materno de infección prenatal; la alta prevalencia de infecciones prenatales en países tropicales y el riesgo de epilepsia ya ha sido descrita en otras poblaciones.…”
Section: Discussionunclassified